Relectura del ministerio ordenado en las comunidades primitivas desde la Evangelii Gaudium. - Huitzacua Hernández, Nancy (2016)
This article attempts to delve into the essence of ordained ministry in the early communities born as a gift of God, a sign of his presence and man's response. The development of this work used genetic-comparative methodology, it attempts an approach to the issue from its roots in the Old Testament, the living priesthood in Jesus and the institution of the priesthood in the early Christian communities, to exercise currently taking account both the role of women as the guidelines of the Apostolic Exhortation Evangelii Gaudium.